Extreme diet without calcium may lead to hyperoxaluria and kidney stone recurrence-A case study - Šálek, Tomáš (Journal of clinical laboratory analysis, 2020)
BACKGROUND: The aim of the study was to present a case study of a 56-year-old woman with hyperoxaluria induced by calcium-free diet that resulted in kidney stone recurrence. METHODS: A 24-hour urine collection and serum tests for kidney stone risk factors identification were performed. The monitoring of urine risk factors was done by untimed urine samples and 24-hour urine collections. Polarized light microscopy was performed for kidney stone analysis. RESULTS: The results of urine collection showed hyperoxaluria of 0.551 mmoL per 24 hours. After adding calcium-containing products to the diet the oxaluria decreased to reference range value of 0.352 mmoL/24 hours and all untimed oxalate to creatinine ratios returned to reference ranges. Polarized light microscopy revealed 100% calcium oxalate kidney stone composition (It was 50% Weddellite and 50% Whewellite). CONCLUSIONS: The case study shows the importance of calcium intake in the prevention of calcium oxalate kidney stone recurrence. Particularly, unsuitable diet without calcium can induce kidney stone recurrence. Knowledge of diet habits is important for interpretation of kidney stone risk factors and their inhibitors excreted in urine.
Keywords: dieta; risk factors; ledvinové kameny; vápník; Middle Aged; hyperoxaluria; diet; recidiva; hyperoxalurie; Kidney Calculi; šťavelan vápenatý; urolithiasis; Calcium; ženské pohlaví; Hyperoxaluria; Humans; Recurrence; lidé středního věku; rizikové faktory; Diet; Calcium Oxalate; Female; Risk Factors; calcium oxalate; lidé